Becoming Entrepreneurs of Connection: How community partnerships shape engagement across difference and anti-poverty commitments - Albert Benson Nylander; James Robert Love; Laura Elizabeth Martin (Michigan Journal of Community Service Learning)
This article contributes to the civic identity development literature by exploring how a scholarship program emphasizing entrepreneurship and economic revitalization can facilitate engagement across difference in pursuit of shared anti-poverty commitments. Drawing on theories of entrepreneurial action, civic identity development literature, and a mixed methods approach, we propose a framework for how students conceptualize identity, race, and poverty as entrepreneurs of connection.